3D bioprinting lobule-like hepatorganoids with induced vascularization for orthotopic implantation - Jianing Yan; Zhichao Ye; Yiwei Lu; Yuyang Yuan; Xiaofeng Wang; Tingting Yan; Jun Yin; Yifan Wang (Materials Today Bio)
Orthotopic implantation in vivo is the ultimate target of tissue-engineering organoids research, aiming to achieve sustaining survival after implantation. However, the limited representation of a complex microenvironment in implanted accepter hampers a comprehensive understanding of long-term maintenance of tissue-engineering organoids, especially in liver. In this research, we developed a 3D bioprinting method using gelatin methacryloyl (GelMA) hydrogel to fabricate lobule-like hepatorganoids, which faithfully mimic the structure of hepatic lobules with lower level of hypoxia (lobule vs 60°, 90°, control; 0.4880 vs 1.009, 0.6778, 0.8704; p < 0.01), high secretion of albumin (lobule vs 60°, 90°, control; 13.47 vs 12.39, 12.65, 10.08 mg/L; p < 0.01) and urea (lobule vs 60°, 90°, control; 5.304 vs 5.233, 4.781, 4.358 mg/L; p < 0.01) in vitro; and promotion of angiogenesis and maintenance of activity following orthotopic implantation. Loaded with a prolonged released system of vascular endothelial growth factor (VEGF) and infused with human umbilical vein endothelial cells (HUVECs), we developed a fabricating method of vascularized lobule-like hepatorganoids (VLH) which possessed promoted vascularization. We identified GAS6/AXL and LAMB3/ITGA3 signaling pathway up-regulated in VLH, which was conducive to vascularization and proliferation. Furthermore, orthotopic implantation model indicated that VLH exhibited prolonged survival in vivo, with elevated level of serological biomarkers and more abundant vascularization in grafts. Eventually, our findings demonstrate that this system effectively forms orthotopic implantation of hepatorganoids and facilitates vascularization, which may notably contribute to the understanding of transplantation, drug screening, and replacement therapy.